Potentiometric Study of Azide Complexes of Iron(III) in Water/THF Medium - Pimenta, Adriano Cesar; Balbo, Valdir Roberto; de Oliveira, Marcelo Firmino; Martins, Fernando Grine; Lourenço, Leandro Maranghetti; de Andrade, José Fernando (Orbital: The Electronic Journal of Chemistry, 2017)
The stepwise formation of iron(III)-azide complexes in water/THF medium has been investigated at 20.0 (± 0.1) °C and 1.00 mol L-1 ionic strength (NaClO4). By the indirect potentiometric method employed, using a glass electrode and under the conditions studied, three mononuclear complexes were successively detected for each water/THF ratio. No evidence of polynuclear species was found. The final analyses of the data for aqueous-tetrahydrofurane (20.0-40.0%, v/v) medium, by solution of adjusted simultaneous equations with Fronaeus function values, led to the overall stability constants varying from b1 = 7.11´103 L mol-1 to b3 = 4.12´1012 L3 mol-3. The results showed that the organic solvent proportion is an important parameter for formation of these complexes. Iron complexes with higher stability were produced in the presence of 40.0% (v/v) tetrahydrofuran. Comparison with literature values suggests that the organic solvent has high influence on the coordination of the metallic ion. DOI: http://dx.doi.org/10.17807/orbital.v9i5.970